PENGARUH MODAL PSIKOLOGIS DAN PENERIMAAN TEKNOLOGI TERHADAP SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK PADA PEGAWAI NEGERI SIPIL PEMERINTAH KABUPATEN PAKPAK BHARAT - Mohd Farouq Hasymi Nasution (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2022)
The policy of implementing an electronic-based government system is carried out to realize clean, effective, transparent, and accountable governance as well as quality and reliable public services. However, the implementation by the Pakpak Bharat Regency Government has not been maximized because they are still used to the old bureaucratic system. This study aims to provide an overview of the capacity of psychological capital and acceptance of technology and to analyze empirically the effect of psychological capital and acceptance of the technology on an electronic-based government system for Civil Servants of the Pakpak Bharat Regency Government. This research method uses quantitative research with multiple linear regression analysis techniques. Research data is generated through a Likert scale which is then processed and analyzed to conclude. The number of samples used in this study was 236 Civil Servants of the Pakpak Bharat Regency Government. The results of this study indicate that in general, civil servants of the Pakpak Bharat Regency Government have a high psychological capital capacity and moderate technology acceptance. The variable of psychological capital has a positive and significant effect on the attitude of using an electronic-based government system. The technology acceptance variable has a negative and significant effect on the attitude of using an electronic-based government system. The variables of psychological capital and acceptance of technology together have a positive effect on the attitude of using an electronic-based government system with a large effect of 36.8%. The Pakpak Bharat Regency Government can increase efforts to facilitate self-development, especially concerning electronic-based government systems for Civil Servants of Sipi Pakpak Bharat Regency Government, and create a work environment with technology that is felt to be easy and useful Keywords: electronic-based government system; Psychological capital; technological acceptance.